Improving the Diagnostic Accuracy of a Stratified Screening Strategy by Identifying the Optimal Risk Cutoff - Brinton, John T. (Cancer Causes Control, 2019)
BACKGROUND: The American Cancer Society (ACS) suggests using a stratified strategy for breast cancer screening. The strategy includes assessing risk of breast cancer, screening women at high risk with both MRI and mammography, and screening women at low risk with mammography alone. The ACS chose their cutoff for high risk using expert consensus. METHODS: We propose instead an analytic approach that maximizes the diagnostic accuracy (AUC/ROC) of a risk-based stratified screening strategy in a population. The inputs are the joint distribution of screening test scores, and the odds of disease given risk score. Using the approach for breast cancer screening, we estimated the optimal risk cutoff for two different risk models: the Breast Cancer Screening Consortium (BCSC) model and a hypothetical model with much better discriminatory accuracy. Data on mammography and MRI test score distributions came from the Magnetic Resonance Imaging Screening Study Group. RESULTS: A risk model with an excellent discriminatory accuracy (c-statistic = 0.947) yielded a reasonable cutoff where only about 20% of women had dual screening. However, the BCSC risk model (c-statistic = 0.631) lacked the discriminatory accuracy to differentiate between women who needed dual screening, and women who needed only mammography. CONCLUSION: Our research provides a general approach to optimize the diagnostic accuracy of a stratified screening strategy in a population, and to assess whether risk risk models lack enough discriminatory accuracy to make stratified screening a reasonable recommendation.